Greenwashing : consumer perspective - Butyrchik, Violetta (2022)
Greenwashing has become a sophisticated issue of green marketing. The demand for green products increases from consumers so does greenwashing. Greenwashing is a misleading practice, which is widely used by companies, and aims to lure customers into assuming they are offered environmental-friendly products.